Screening for elevated levels of fear-avoidance beliefs regarding work or physical activities in people receiving outpatient therapy. - Hart DL; Werneke MW; George SZ; Matheson JW; Wang Y; Cook KF; Mioduski JE; Choi SW (Physical Therapy, 2009)
BACKGROUND: Screening people for elevated levels of fear-avoidance beliefs is uncommon, but elevated levels of fear could worsen outcomes. Developing short screening tools might reduce the data collection burden and facilitate screening, which could prompt further testing or management strategy modifications to improve outcomes. OBJECTIVE: The purpose of this study was to develop efficient yet accurate screening methods for identifying elevated levels of fear-avoidance beliefs regarding work or physical activities in people receiving outpatient rehabilitation. DESIGN: A secondary analysis of data collected prospectively from people with a variety of common neuromusculoskeletal diagnoses was conducted. METHODS: Intake Fear-Avoidance Beliefs Questionnaire (FABQ) data were collected from 17,804 people who had common neuromusculoskeletal conditions and were receiving outpatient rehabilitation in 121 clinics in 26 states (in the United States). Item response theory (IRT) methods were used to analyze the FABQ data, with particular emphasis on differential item functioning among clinically logical groups of subjects, and to identify screening items. The accuracy of screening items for identifying subjects with elevated levels of fear was assessed with receiver operating characteristic analyses. RESULTS: Three items for fear of physical activities and 10 items for fear of work activities represented unidimensional scales with adequate IRT model fit. Differential item functioning was negligible for variables known to affect functional status outcomes: sex, age, symptom acuity, surgical history, pain intensity, condition severity, and impairment. Items that provided maximum information at the median for the FABQ scales were selected as screening items to dichotomize subjects by high versus low levels of fear. The accuracy of the screening items was supported for both scales. LIMITATIONS: This study represents a retrospective analysis, which should be replicated using prospective designs. Future prospective studies should assess the reliability and validity of using one FABQ item to screen people for high levels of fear-avoidance beliefs. CONCLUSIONS: The lack of differential item functioning in the FABQ scales in the sample tested in this study suggested that FABQ screening could be useful in routine clinical practice and allowed the development of single-item screening for fear-avoidance beliefs that accurately identified subjects with elevated levels of fear. Because screening was accurate and efficient, single IRT-based FABQ screening items are recommended to facilitate improved evaluation and care of heterogeneous populations of people receiving outpatient rehabilitation.